Information and communication technology and public innovation : assessing the ICT-driven modernization of public administration - Bekkers, V. J. J. M.; Duivenboden, Hein van; Thaens, Marcel (Innovation and the public sector, 2006)
The modernization of public administration is a recurring theme on the political and public agenda in many countries. This book demonstrates how public administration organizations try to adapt to changing circumstances in their environment in order the secure their legitimacy, presenting a number of case studies.